PENGARUH MEDIA TANAM DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL MENTIMUN (Cucumis sativus L.) SECARA HIDROPONIK - Putri Erfiani Erfiani; Armaini Armaini; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Growing media and nutrients are important factors of cucumber cultivation in hydroponic techniques. The use of growing media and different nutritional sources is thought to affect its growth, so a research that combines these two factors was carried out in aims to find out the suitable growing media and nutrients for growth of cucumber plant in hydroponic techniques. The growing media that used in this research were husk charcoal and dried bamboo leaves, while the nutritional source is liquid organic fertilizer (LOF) that has been destructed and un-destructed. The research was conducted using completely randomized design (CRD) factorial with observed parameters such as first day of harvesting, number of fruits per plant, fresh fruit weight per plant, weight per fruit, fruit length, fruit diameter, stover wet weight, stover dry weight, root canopy ratio, ratio of fruit weight per plant with stover wet weight. The results of the research showed that the treatments of different growing media impacted on all observed parameters except for first day of harvesting.The treatment of LOF affected all observed parameters except for first day of harvesting. The treatment of growing media of dry bamboo leaves with destructed LOF is the best treatment and increased the number of fruits per plant, fresh fruit weight per plant, fruit length, fruit diameter, stover wet weight and stover dry weight. The treatment of LOF and destructed LOF showed the same results on growth and yield, so that Super Bionic LOF tended as nutrients and there was no effect of PGRs (Plant Growth Regulators) on growth and yield of cucumber plants in hydroponic techniques. Keywords: hydroponics, liquid organic fertilizer, bamboo leaves, nutrient